An Inverse Method to Reconstruct Complete Stiffness Information of Rubber Bushing. (26th September 2013) - Lei, Gang; Chen, Qian; Liu, Ying; Jiang, Jingjing
Abstract : A specific rubber bushing, with only radial and axial stiffness data having been acquired, is studied. In terms of the hyperelastic material of this bushing, three-term Ogden law is utilized as the material constitutive model which requires to be characterized. Without the material mechanical tests provided, a parameter identification method is proposed for searching a group of acceptable parameters which are able to model rubber-like material of this rubber bushing. In this case, based on the nonlinear finite element analysis method and optimization technique, the parameters of material law are determined, and the rotational stiffness of this bushing is also evaluated. The complete stiffness information has been established.